DEVELOPMENT OF TECHNICAL CREATIVITY OF STUDENTS IN PHYSICS LESSONS USING DEVICES OF ALTERNATIVE ENERGY SOURCES (American Journal of Research in Humanities and Social Sciences, 2022)
This article describes the possibilities of using alternative energy sources in the development of technical creativity of students in physics circles, the procedure for implementing the plan for designing devices in a circle. Also, a calendar-thematic plan of a physics circle was developed to develop the technical creativity of students based on alternative energy sources, the possibility of developing technical creativity of students on the example of a project to provide energy at home based on solar panels.